IMAGERY ANALYSIS IN SEVEN SELECTED POEMS BY HENRY WADSWORTH LONGFELLOW - Suyudi Suyudi (Pujangga: Jurnal Bahasa dan Sastra, 2021)
ABSTRACTThis research analyzes imagery in seven selected poems by Henry Wadsworth Longfellow. The seven selected poems of Henry Wadsworth Longfellow are as follow “ The Rainy Day, Prelude, the light of stars, a Dutch picture, a summer day by the sea, afternoon in February, the arsenal at Springfield.” Descriptive qualitative method and structural approach are used to find out types of imagery that are used in seven selected poems by Henry Wadsworth Longfellow. The researcher then collected the data from the seven poems mentioned. The technique of analyzing data is by reading the poem and using structural approach to find types of imagery that are used in poems “ The Rainy Day, prelude, the light of stars, a Dutch picture, a summer day by the sea, afternoon in February, the arsenal at Springfield”. This research on the imagery analysis in seven selected poems by Henry Wadsworth Longfellow has found five types of imagery. This research found 114 words of visual imagery, 36 words of auditory imagery, 7 words of tactile imagery, 7 words of kinesthetic imagery, 13 words of organic imagery. The most dominant types of imagery in this research is visual imagery.Keywords: Poetries, imagery, Henry Wadsworth Longfellow